Little red wagon [videorecording (DVD)] - Gunn, Anna, 1968-; Canterbury, Chandler, 1998-; O'Connor, Frances, 1967-; Anspaugh, David (Distributed exclusively in Canada by Phase 4 Films, 2013)
Based on the inspirational true story of eight-year-old Zach Bonner on his quest to change the world with nothing more than his beat-up red wagon and a blazing spirit of philanthropy. When Zach sets out to help homeless children in America in the wake of Hurricane Charley, by walking from his house in Tampa, Florida to the White House, he must overcome bureaucrats and blisters and capture the hearts of his fractured family and the entire nation.